THE APPLICATION OF THE NUMBER HEAD TOGETHER MODEL ASSISTED BY AUDIO VISUAL MEDIA IN INCREASING STUDENTS' INTEREST IN LEARNING IN SD NEGERI 41/II LAMAN PANJANG ON IPAS LEARNING: PENERAPAN MODEL NUMBER HEAD TOGETHER BERBANTU MEDIA AUDIO VISUAL DALAM MENINGKATKAN MINAT BELAJAR SISWA DI SD NEGERI 41/II LAMAN PANJANG PADA PEMBELAJARAN IPAS - Anisa Anisa; Megawati Megawati; Abdullah Abdullah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study was motivated by the low learning interest and participation of fourth-grade students at SD Negeri 41/II Laman Panjang in the subject of Natural and Social Sciences (IPAS). Conventional teaching methods and limited learning media made it difficult for students to understand the material and actively participate in discussions and group activities. This study aims to investigate how the implementation of the Number Head Together (NHT) model assisted by audiovisual media can improve the learning process and students’ learning interest in IPAS. This research employed a Classroom Action Research (CAR) approach with 13 fourth-grade students as the subjects. The study was conducted in two cycles, with each cycle consisting of two meetings. Research instruments included teacher observation sheets, student observation sheets, and a learning interest questionnaire. The results showed significant improvements in both aspects observed. In terms of the teacher’s performance, the implementation of teaching indicators increased from 55.56% in the first meeting of cycle I to 94.44% in the second meeting of cycle II. Regarding student activity, learning participation improved from mostly adequate/good in cycle I to good/very good in cycle II. Students’ learning interest also increased; in cycle I, 23.1% of students were in the very good category and 46.2% in the good category, while in cycle II, 38.5% were very good and 46.2% were good, with no students in the low category. Based on these findings, it can be concluded that the implementation of the Number Head Together model assisted by audiovisual media is effective in enhancing the learning process and increasing the learning interest of fourth-grade students at SD Negeri 41/II Laman Panjang.